Radical α-C–H Cyclobutylation of Aniline Derivatives - Pratt, Cameron J.; Aycock, R. Adam; King, Max D.; Jui, Nathan T. (Synlett, 2020)
A catalytic system has been developed for the direct alkylation of α-C–H bonds of aniline derivatives with strained C–C σ-bonds. This method operates through a photoredox mechanism in which oxidative formation of aminoalkyl radical intermediates enables addition to a bicyclobutane derivative, giving rise to α-cyclobutyl N-alkylaniline products. This mild system proceeds through a redox- and proton-neutral mechanism and is operational for a range of substituted arylamine derivatives.
Keywords: photoredox reaction; catalysis; C–C bond activation; anilines; alkylation; iridium catalysis